Long-term virological outcomes in women who started option B+ care during pregnancy for prevention of mother-to-child transmission of HIV in Dar es Salaam, Tanzania: a cohort study. Issue 5 (May 2021) - Lyatuu, Goodluck W; Mwashemele, Shally Z; Urrio, Roseline; Naburi, Helga; Kashmir, Nassir; Machumi, Lameck; Kibao, Ayoub; Sellah, Ziada; Ulenga, Nzovu; Orsini, Nicola; Biberfeld, Gunnel; Kilewo, Charles; et al.
Summary: Background: Option B+ marked a milestone in prevention of mother-to-child transmission (PMTCT) of HIV by recommending lifelong antiretroviral therapy (ART) for all pregnant women with HIV. Nevertheless, concerns remain regarding long-term outcomes in settings with a high HIV burden. We analysed long-term virological outcomes in women enrolled on option B+ in Tanzania. Methods: In this prospective cohort study, we extracted data for pregnant women with HIV starting PMTCT care between Oct 1, 2014, and Sept 30, 2016, in routine health-care settings in Dar es Salaam, Tanzania, from national HIV and district health information system databases. We then excluded women who exited study sites before 6 months of ART follow-up and women who did not have a viral load test. Women were followed up until March 8, 2019. We used Poisson generalised estimating equations to examine trends in HIV viral suppression (<400 copies per mL) and virological failure (≥400 copies per mL), reporting relative risks (RRs) and 95% CIs adjusted for maternal age, gestational age, and several clinical characteristics. Findings: We identified 15 586 pregnant women with HIV, of whom 10 161 were eligible for follow-up. Women were followed up for a median of 37 months (IQR 31–45) and a maximum of 53 months. The median age at PMTCT initiation was 31 years (IQR 27–35). At PMTCT enrolment, 1245 (17·0%) of 7318 women with available data were in their third trimester, 4901 (48·2%) of 10 161 women started ART at least 1 month before PMTCT enrolment, and 3380 (33·4%) of 10 131 women with available data had advanced HIV. Overall, a viral suppression rate of 88·2% (95% CI 87·8–88·7) was observed over the entire follow-up period, ranging from 85·1% (84·3–85·9) in viral load tests done at 0–11 months to 90·6% (89·7–91·4) at 36 months or longer since PMTCT enrolment. In a complete-case analysis (ie, including patients with <30% missing data; n=7306), the risk of virological failure among women who remained in HIV care decreased over time (adjusted RR 0·87 [95% CI 0·80–0·95] at 12–23 months since PMTCT enrolment; 0·65 [0·59–0·72] at 24–35 months; and 0·63 [0·55–0·71] at ≥36 months vs at 0–11 months). Younger women (aged <20 years: 1·76 [1·40–2·23] vs aged 30–39 years) and those starting PMTCT late in pregnancy (third trimester: 1·28 [1·10–1·50] vs first trimester) or with advanced HIV (1·33 [1·16–1·51] vs without advanced HIV) had increased risk of virological failure. Women who attended an antenatal care facility where more than 50% of attendees received couples HIV testing had a decreased risk of virological failure (adjusted RR 0·81 [0·65–0·99] vs <50% having couples testing). Interpretation: High rates of viral suppression among women starting option B+ who remain in HIV care are sustainable, and might increase, at least up to 53 months. This rate might be further improved by addressing challenges of adolescent mothers, late presenters, and couples HIV testing at antenatal care. Funding: Swedish International Development Agency.